Clinton [videorecording (DVD)] - Goodman, Barak; Goodman, Barak; Goodman, Barak; Scott, Campbell (PBS Distribution, 2012)
In the tradition of American Experience's acclaimed Presidents series, Clinton provides an intimate, honest, balanced look at the 42nd president's life, career, and legacy. The definitive biography tracks William Jefferson Clinton from his difficult childhood in Hope, Arkansas, through his meteoric rise in state politics, to the highs and lows of his tumultuous presidency.